Patient prognosis after relief of obstruction - R Danarto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
ABSTRACTObstructive uropathy may lead to irreversible kidney damage. The insertion of ureteral stent is one of procedure to relief obstruction and prevent further kidney damaged, septicemia as well as urosepsis. A study to evaluate the predictive factor of urinary diversion in improving kidney function is needed. This study aimed to assess prognosis factors post-relief of obstruction in patients with uropathic obstruction focusing on kidney function recovery. This was a retrospective cohort study conducted at An-Nur Private Hospital in Yogyakarta Special Region, Indonesia using the medical record of patients with obstructive uropathy whom underwent DJ Stent insertion from a period of 2011 to 2015. The data of clinical assessment, laboratory and radiologic examination data were collected and analyzed using Chi square or student t test. A total 59 patients with obstructive uropathy aged around 50.9 years whom underwent DJ Stent were involved in this study. The results showed that release of obstruction with the installation of ureteral stents was significantly able to improve kidney function. The duration of obstruction, etiology, and hemoglobin (Hb) levels were associated with creatinine levels, whereas gender, urinary tract infection (UTI) and comorbid were not. In conclusion, prognosis factors of postrelief obstuction are duration of obstruction, etiology of obstruction and Hb levels before the release of obstruction